PERANCANGAN PEMANTAUAN SUHU CLIMATIC CHAMBER BERBASIS ARDUINO DILENGKAPI HEATER DAN PELTIER - Muhammad Ulin Nuha ABA; Bayu Wahyudi; Mohamad Sofie (Elkom : Jurnal Elektronika dan Komputer, 2021)
The climatic chamber is a calibration medium for the thermohygrometer. This simple climatic chamber was built using the Arduino uno, DHT22 sensor, heater, and peltier. The climatic chamber was designed and manufactured well and cheaply. Climatic chamber testing of the design results is carried out to determine the success rate of the tool. Tests are carried out using the Madgetech data logger tool through monitoring or monitoring of temperature within a certain period of time. The results of temperature monitoring at two observed values, namely temperatures of 250C to 300C and temperatures of 300C to 350C, showed good results with the corresponding rhythm of temperature increase and temperature decrease. It's just that the decrease in temperature still takes longer than the increase in temperature. This shows that the heater can be said to be working optimally and the peltier is not fully working. So it is necessary to do further studies related to the peltier for the climatic chamber both in terms of number and characteristics.